Human biochemistry - Litwack, Gerald (Academic Press, 2022)
"Human Biochemistry' includes clinical case studies and applications that are useful to medical, dentistry and pharmacy students. It enables users to practice for future careers as both clinicians and researchers. The book also provides extensive online support for students to assist with further understanding and comprehension of advanced concepts, including sample questions that will help them prepare for medical exams. In addition, instructor's ancillaries include PowerPoint presentations and testbanks. Offering immediate application of biochemical principles into clinical terms in an updated way, this book is the unparalleled textbook for medical biochemistry courses in medical, dental and pharmacy programs."-- $c Provided by publisher.